2016
DOI: 10.1016/j.yebeh.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

A lack of clinically apparent vision loss among patients treated with vigabatrin with infantile spasms: The UCLA experience

Abstract: We found that the risk of clinically apparent vision loss is quite low among young children treated for infantile spasms. Our estimate of risk contrasts with prior studies and likely reflects our ascertainment of vision loss without the aid of perimetry or serial ERG, the short treatment duration, and the relatively young age of our patients. In the treatment of infantile spasms, risk-benefit assessment should consider both the low prevalence of ERG-identified VAVFL among patients with brief (<6-9months) expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…In a pair of contemporary studies, the risk of VAVFL as determined by kinetic perimetry was <10% among children treated for <12 months, and the risk of electroretinographically defined retinotoxicity was <6% among children treated for <6 months . In our own experience, the risk of clinically apparent vision loss approaches zero with relatively short courses of therapy . Nevertheless, there are no available data confirming that the risk of relapse of infantile spasms is diminished by extended courses of vigabatrin, and there is little guidance as to what constitutes an ideal treatment duration.…”
Section: Discussionmentioning
confidence: 83%
“…In a pair of contemporary studies, the risk of VAVFL as determined by kinetic perimetry was <10% among children treated for <12 months, and the risk of electroretinographically defined retinotoxicity was <6% among children treated for <6 months . In our own experience, the risk of clinically apparent vision loss approaches zero with relatively short courses of therapy . Nevertheless, there are no available data confirming that the risk of relapse of infantile spasms is diminished by extended courses of vigabatrin, and there is little guidance as to what constitutes an ideal treatment duration.…”
Section: Discussionmentioning
confidence: 83%
“…It is notable that the impression that hormonal therapy exhibits superior efficacy does not necessarily generalize to children with TSC. Although a large‐scale trial of VGB versus high‐dose hormonal therapy has not been undertaken in a TSC cohort, several studies indeed suggest that response to VGB is substantially higher among patients with TSC in comparison to patients with other etiologies . Accordingly, there is broad consensus that patients with IS in the setting of TSC should receive first‐line treatment with VGB …”
Section: Vigabatrinmentioning
confidence: 99%
“…Although a large-scale trial of VGB versus highdose hormonal therapy has not been undertaken in a TSC cohort, several studies indeed suggest that response to VGB is substantially higher among patients with TSC in comparison to patients with other etiologies. 32,35,36 Accordingly, there is broad consensus that patients with IS in the setting of TSC should receive first-line treatment with VGB. 15 Despite this established efficacy, the use of VGB has been limited by reports of retinopathy manifesting with permanent bilateral concentric peripheral visual field defects in both adults 37 and children.…”
Section: Hormonal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…VGB is currently used as adjuvant therapy for refractory epilepsies, complex partial seizures, secondarily generalized seizures, infantile spasms, and is under active investigation in tuberous sclerosis complex . However, an extensive body of literature suggests that VGB is associated with peripheral visual field defects (pVFD), but others have suggested that VGB ocular toxicity correlates with pre‐existing anomalies, both structural and genetic . The occurrence of permanent visual field constriction in patients receiving VGB is ~6‐7%) .…”
Section: Discussionmentioning
confidence: 99%